1993
DOI: 10.1038/bjc.1993.192
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive assessment of health status in survivors of childhood cancer: application to high-risk acute lymphoblastic leukaemia

Abstract: Summary The health status of 69 survivors of high-risk acute lymphoblastic leukaemia (ALL) is assessed using a multi-attribute classification system. Seven attributes are included: sensation, mobility, emotion, cognition, self-care, pain and fertility. Three to five levels of functioning are defined for each attribute. Comprehensive health states are described as a specific combination of seven attribute levels. The system captures combinations of sequelae. The system provides a compact but comprehensive tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 27 publications
1
53
1
1
Order By: Relevance
“…Most limitations mentioned are lessened or overcome by the large number of patients for a rare disease, enhancing the power of the study and compensating for missing data. Other strengths are the longitudinal character of the study, with duration of 12½ years, and the use of standardized instruments that have been extensively validated in diverse populations 18, 27, 30, 44, 45. The latter also enables the comparison of the burden of VWM to other patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most limitations mentioned are lessened or overcome by the large number of patients for a rare disease, enhancing the power of the study and compensating for missing data. Other strengths are the longitudinal character of the study, with duration of 12½ years, and the use of standardized instruments that have been extensively validated in diverse populations 18, 27, 30, 44, 45. The latter also enables the comparison of the burden of VWM to other patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used extensively as an outcome measure, also for neurological disorders, in patients from age 1 year 18, 19, 20, 21. It comprises distinct attributes of health status that enable valuation of function‐specific scores (single‐attribute utility scores) and generic multiattribute preference‐based measures of quality of life (HUI Health Index) at a point in time.…”
Section: Methodsmentioning
confidence: 99%
“…When comparing these two groups in terms of their PIE scores and other measures, differences were found on one subscale only. Those who had completed treatment reported that the impact of the illness on integration in school was greater than for those still on maintenance treatment (mean (SD) [2][3][4][5] (1-6), p<005).…”
Section: Treatment Statusmentioning
confidence: 99%
“…The HUI2 was originally developed to assess survivors of childhood cancer, 19 but has since been used to evaluate functional outcome in other pediatric populations. 17,18,[20][21][22] The HUI2 can describe 24,000 unique health states.…”
Section: Quality Of Life After Pediatric Liver Transplantmentioning
confidence: 99%